Svensk franskklassicism? Ett transkulturellt drama - Albrektson, Anna (1700-tal: Nordic Journal for Eighteenth-Century Studies, 2025)
This article analyses the debate between Olof Bergklint and Eric Brander (ennobled Skjöldebrand) about Swedish classicist tragedy during the Swedish era of Liberty. The debate expands on the use of Old Norse subjects for tragedy, and the arising difficulties concerning probability, vraisemblance, and decorum, caused by historical and cultural distance. Questions of style initiate a debate on how to transform classical norms into a high style in Swedish verse. From a transcultural perspective, the advocated Swedish version of tragedy during the period is described as a hybrid, incorporating both the strict rules of Racinian tragedy and Swedish re-interpretations of Voltaire, classical authorities, and models from several European language areas. The transcultural approach contributes to a reinterpretation of the Swedish debate, and highlights the asymmetry of transcultural processes, by replacing the notion of ”influence” with hybridity.